Analisis Kelayakan Bisnis Makanan Dan Minuman Kekinian Untuk Generasi Z - Alfina Handayani; Lia Apriliani; Dwi Astuti (CV. ITTC INDONESIA, 2025)
The feasibility analysis of contemporary food and beverage outlets for Generation Z highlights the dynamics of consumer behavior, marketing trends, and key factors influencing purchasing decisions. Generation Z, born between the mid-1990s and early 2010s, is characterized by a strong connection to digital technology and social media. This generation exhibits preferences for healthy, sustainable, and eco-friendly products, as well as unique experiences aligned with social values. Social media-based marketing and culturally relevant strategies are critical for capturing their attention. Challenges such as balancing product quality, competitive pricing, and strategic location are essential issues that entrepreneurs must address. By understanding consumption trends, generational values, and leveraging digital innovation, food and beverage businesses hold significant potential for growth in this competitive market.